Antisense oligonucleotide-induced alternative splicing of the APOB mRNA generates a novel isoform of APOB - Krainer, Adrian R. (2011)
Background: Apolipoprotein B (APOB) is an integral part of the LDL, VLDL, IDL, Lp(a) and